1982
DOI: 10.1002/j.1537-2197.1982.tb13331.x
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Protease‐digestible Material in Golgi Vesicles During Endosperm Development of Selected Cereals

Abstract: The presence of dictyosomes secreting densely stained vesicles throughout endosperm protein body formation was confirmed for four cereals (rice, Oryza sativa L.; hard red winter wheat, Triticum aestivum L.; winter feed barley and spring malting barley, Hordeum vulgare L.; oats, Avena sativa L.). The contents of the Golgi vesicles and protein bodies were digested with proteases for all cereals except rice. It was found in the case of rice that OsO4 altered the proteins in the Golgi apparatus and protein bodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Previously, we have shown ' for wheat and other cereals that the Golgi vesicles contents are protease digestible (Bechtel and Gaines, 1982). In addition, we have shown that the protein granules are protease digestible (Bechtel et al, 1982). We have been able to demonstrate the presence of Golgi apparatus in wheat starchy endosperm until 28 DAF (in which 34 DAF is maturity, the harvest date).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Previously, we have shown ' for wheat and other cereals that the Golgi vesicles contents are protease digestible (Bechtel and Gaines, 1982). In addition, we have shown that the protein granules are protease digestible (Bechtel et al, 1982). We have been able to demonstrate the presence of Golgi apparatus in wheat starchy endosperm until 28 DAF (in which 34 DAF is maturity, the harvest date).…”
Section: Discussionmentioning
confidence: 59%
“…The results of this study indicated that the Golgi apparatus began to secrete electron-opaque vesicles at the time of protein body initiation. Previously, we have shown ' for wheat and other cereals that the Golgi vesicles contents are protease digestible (Bechtel and Gaines, 1982). In addition, we have shown that the protein granules are protease digestible (Bechtel et al, 1982).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…DISCUSSION Protein digestion techniques have been employed for many years for determining the composition of cellular structures that have been prepared for electron microscopy. The validity of these techniques, however, has been questioned by many workers (Anderson & Andr6, 1968;Bechtel & Gaines, 1982;Behnke, 1975;Weintraub, Ragetli & Schroeder, 1971). Bechtel & Gaines (1982) listed several factors that may affect enzymic extraction of proteinaceous components, including: (1) exposing sections to the electron beam prior to extraction; (2) using osmium tetroxide as a fixative; and (3) using an embedding medium that penetrates the tissue so well that it prevents the enzyme from reaching the substrate.…”
Section: Nuclear Crystalloids In Sieve Elementsmentioning
confidence: 99%